Can microscale fracture tests provide reliable fracture toughness values? A case study in silicon. Issue 5 (9th February 2015) - Jaya, Balila Nagamani; Kirchlechner, Christoph; Dehm, Gerhard
Abstract: Abstract : Fracture toughness testing of materials at the micrometer scale has become essential due to the continuing miniaturization of devices accompanied by findings of size effects in fracture behavior. Many techniques have emerged in the recent past to carry out fracture toughness measurements at the relevant micro and nanolength scales, but they lack ASTM standards that are prescribed for bulk scale tests. Also, differences in reported values arise at the microscale due to the sample preparation technique, test method, geometry, and investigator. To correct for such discrepancies, we chose four different fracture toughness test geometries in practice, all of them micromachined in the focused ion beam (FIB), to investigate the fracture toughness of Si(100) at the micrometer scale. The average K IC that emerges from all four cases is a constant (0.8 MPa m 1/2 ). The advantages and limitations of each of these geometries in terms of test parameters and the range of materials that can be tested are discussed.